A 3D printed wound cooling system incorporated with injectable, adsorbable, swellable and broad spectrum antibacterial scaffolds for rapid hematischesis processing. Issue 37 (6th September 2018) - Ai, Fanrong; Liu, Tingwu; Liu, Yu; Yang, Kang; Liu, Yishen; Wang, Wenyan; Yuan, Fushan; Dong, Lina; Xin, Hongbo; Wang, Xiaolei
Abstract : Uncontrolled hemorrhage remains a leading cause of early death after trauma, and contamination further challenges the wounded. Abstract : Uncontrolled hemorrhage remains a leading cause of early death after trauma, and contamination further challenges the wounded. In the present study, silver nanocluster (or silver nanoparticle) decorated rapidly swellable hemostatic scaffolds (AgNCs/RSHs and AgNPs/RSHs) were prepared. A 3D printed injectable wound cooling hemostatic (IWCH) system was accordingly designed and implemented to realize the relative rapid hemostasis operation. The obtained AgNCs/RSHs and AgNPs/RSHs exhibited excellent biocompatibility and broad-spectrum antibacterial properties including drug resistant strains. In a rabbit femoral vascular injury model, bleeding could be instantly stopped in 10 seconds by using IWCHs. The present study provided a new insight into the development of rapid hemostatic biomaterials to realize a quick, precise and simplified hemostasis operation in less time and with less bleeding.